An extraordinary wave of SARS-CoV2, the youngest and the least serious - Elena Justribó; Elena Justribó; Alberto Falcon; Maria José Ruiz-Vert; Juliana Porque; Silvia Gros; Silvia Gros; Oriol Yuguero; Oriol Yuguero (Frontiers Media S.A., 2023)
The second wave of SARS-CoV2 in our health region began at the end of June 2020 coinciding with the widespread decrease in cases in all areas of Catalonia. This resulted in the relaxation of measures that coincided with the end of the school year and the arrival of seasonal workers for the fruit-picking campaign. This led to a rapid increase in cases that culminated in perimeter confinement of the Segrià in July 2020, the only such measure imposed in the whole of Spain that month. This increase in cases was attributed to the influx of agricultural workers with a change of trend in the age of persons affected that had until then consisted mainly of older people. Simultaneously, in other areas of Catalonia the number of cases had dropped dramatically.